Five Interpersonal Factors Are Predictive of the Response to Treatment of Major Depression With Antidepressants in Primary Care - Salazar-Fraile, José; Sempere-Verdú, Ermengol; Pérez-Hoyos, Santiago; Tabarés-Seisdedos, Rafael; Gómez-Beneyto, Manuel (Frontiers in Psychiatry, 2018)
Introduction: Factors relating to the interpersonal relationship between the patient and their physician and social environment are important components, which contribute to their response to treatment for major depressive disorder. This study aimed to assess the influence of optimism, perfectionism, therapeutic alliance, empathy, social support, and adherence to medication regimen in the response to antidepressant treatments in the context of normal primary care clinical practice. Method: We conducted a prospective study in which 24 primary care physicians administered sertraline or escitalopram to 89 patients diagnosed with major depressive disorder. The response to treatment and remission of the episode was assessed at 4 and 12 weeks by Cox regression. The effect of adherence to the medication regimen was assessed by multiple regression statistical techniques. Results: Adherence to medication (HR = 0.262, 95% CI = 0.125–0.553, p < 0.001) and patient perfectionism (HR = 0.259, 95% CI = 0.017–0.624, p < 0.01) negatively predicted the initial response to treatment, whereas patient optimism (HR = 1.221, 95% CI = 1.080–1.380, p < 0.05) positively predicted it. Patient optimism (HR = 1.247, 95% CI = 1.1–1.4, p < 0.05), empathy perceived by the patient (HR = 1.01, 95% CI = 1001–1002, p < 0.05), and therapeutic alliance (HR = 1.02, 95% CI = 1001–1.04, p < 0.05) positively predicted episode remission, while patient perfectionism (HR = 0.219, 95% CI = 0.093–0.515, p < 0.001) and low adherence to the treatment regimen (HR = 0.293, 95% CI = 0.145–0.595, p < 0.001) negatively predicted it. Finally, social support (p < 0.01) and therapeutic alliance (p < 0.05) predicted adherence to the medication regimen. Conclusions: In addition to taking the antidepressant drug, other factors including the personal interactions between the patient with their primary care physician and with their social environment significantly influenced the patients’ initial response and the final rate of episode remission.